Development of laser ablation dielectric barrier discharge optical emission spectrometry (LA-DBD-OES) for direct determination of sulphur and chloride in the condensed phase and its application in pharmaceutical analysis. Issue 24 (23rd November 2021) - Ding, Xuelu; Geng, Chaoqun; Zhai, Suhan; Cao, Xiaoyan; Shi, Zhenyan; Liu, Kun
Abstract : The implementation of laser-assisted sampling and atmospheric pressure plasma-based atomization/excitation for optical emission spectrometric determination of sulfur and chloride in organic compounds in the condensed phase. Abstract : An infrared laser (808 nm) has been coupled with dielectric barrier discharge (DBD) for optical emission spectrometric determination of S and Cl in organic compounds. The use of a continuous wave IR laser with an output power of 1–2 W allows volatilization of analytes from condensed surfaces. Analytes thermally delivered to the gas phase are excited and atomized by the DBD plasma triggered by an alternating voltage of 10 kV at 25 kHz under atmospheric pressure. Direct analysis of S- and Cl-containing organics in manufactured tablets by measuring the S and Cl emissions resulted in a dynamic range of 0.5%–20% with linearities ( R 2 ) above 0.93 and limits of detection (LODs) in the μg g −1 range. The detection precision was examined by measuring inter-day and intra-day reproducibilities, leading to relative standard deviations (RSDs) ranging from 4.6% to 15.0%. The feasibility of LA-DBD-OES was further demonstrated with commercial pharmaceutical tablets of sulfadiazine (SDZ) and chloramphenicol (CAP). There is the potential for probing the tablet uniformity by monitoring the elemental emissions of S and Cl. Quantitative results of the commercial tablets were consistent with the indication amounts and were verified by HPLC measurements. All these results suggest the proposed methodology as a promising tool for online analysis of solids and pharmaceutical tablets with minimal sample treatments and rapid detection response.